PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAI (TEAM ASSISTED INDIVIDUALIZATION ) DALAM MENINGKATKAN KEAKTIFAN BELAJAR DAN PEMAHAMAN KONSEP PADA PELAJARAN MATEMATIKA SISWA KELAS XI DI SMK NEGERI 1 JAYAPURA - Kurniati, Ririn (Magister Pendidikan IPA, UNCEN, 2015)
This Research is suppose to : (1) know model application type TAI on learning cooperative to improve the active learning and understanding concept on math of student in grade XI software engineering in vocational school 1 Jayapura (2) know the distinguish active learning between class which using model cooperative learning type TAI to class which using model conventional in grade XI of software engineering in vocational school 1 Jayapura. This Research using Nonequivalent Control Group Design. We take the population in all grade XI of vocational school 1 Jayapura 2012/2013. We use sampling purposive technique in this research. Software engineering A dan B grade XI as a class control. Collecting data using test method and untest. Technique analyse by normality test, homogeneity test, N Gain and difference test and hypothesis test by Independent t-Tes. The Result indicate that there are increasing concept understand on items of line and deret after applying the model cooperative learning type TAI grade XI software engineering in vocational school 1 Jayapura and the distinguish active learning between class which using model cooperative learning type TAI to class which using conventional learning of software engineering student grade XI in vocational school 1 Jayapura. In other word, application model cooperative learning type TAI of student software engineering grade XI in vocational school 1 Jayapura 2012/2013 able to improve the active learning and understanding concept on math. Keyword: student active learning, concept understanding.